An evaluation of the U.P. College of Science Library facilities a users' perception - Bernal, Richard F. (2009)
This paper focuses on two elements of performance of the library. These are technical and functional elements of performance deal with survival issues such as health, safety and security and performance of building systems. These elements can be characterized as the background environment for carrying out activities while the functional elements deal with fit between the building and the users' activities. The functional elements of a building support the activities carried out with it. They must be responsive to the specific needs of the organization and the occupants, both quantitative and qualitative. These elements for academic and research libraries are discussed in this study.